An Internal Limiting Membrane Plug and Gas Endotamponade for Recurrent or Persistent Macular Hole - Fabrizio Giansanti; Ruggero Tartaro; Tomaso Caporossi; Daniela Bacherini; Alfonso Savastano; Francesco Barca; Stanislao Rizzo (Journal of Ophthalmology)
Introduction. Recurrent or persistent macular holes (MHs) are rare today due to the tendency to carefully peel the internal limiting membrane. Conversely, their treatment is still a challenge for a vitreoretinal surgeon. Materials and Methods. This is a retrospective, consecutive, and nonrandomized study of patients affected by recurrent or persistent MHs treated using small-gauge pars plana vitrectomy (25- or 23-gauge) and an autologous ILM plug, at the Eye Clinic of Azienda Ospedaliera Universitaria Careggi (Florence, Italy) between January 2016 and May 2018. We included 8 eyes of 8 patients in the study. Five patients had a recurrent MH while 3 had a persistent MH. The case series includes patients with myopic eyes and with large macular holes (>400 μ). Patients were followed up with ophthalmoscopic examinations and swept-source optical coherence tomography (SS-OCT). Results. The mean age of the patients was 74 years (±4.81 standard deviation (SD)), 3 patients were men and 5 women. The average axial length was 26.28 mm (±2.84 SD). Four patients had an AL ≧ 26 mm. The mean MH diameter was 436.5 (±49.82 SD). Average preoperative best-corrected visual acuity (BCVA) was 0.81 logMAR (±0.16 SD) and 20/125 Snellen. The ILM plug has been found integrated in the MH in all the follow-ups. Conclusion. In our study, an ILM autologous macular transplant was used successfully in 5 cases of macular hole recurrence and 3 cases of macular hole persistence. The anatomical success was achieved in all the cases; 4 patients improved their BCVA, and 4 patients maintained it. No macular alterations such as RPE or retinal atrophy/dystrophy were observed after 6 months.